Assessment of changes in population aging of Polish provinces in 2002, 2010 and 2017 using the hybrid approach - Walesiak, Marek; Dehnel, Grażyna (Ocena zmian w procesie starzenia się ludności województw Polski dla lat 2002, 2010 i 2017 z wykorzystaniem podejścia hybrydowego, 2019)
The study investigates the variation in population ageing in Polish provinces in 2002, 2010 and 2017. Population ageing was assessed using the median age, proportion of elderly people, double ageing index, ageing index, and old-age dependency ratio. The authors took into account causes that explain changes occurring at the bottom and at the top of the population pyramid. By applying the hybrid approach combining multidimensional scaling with linear ordering (the two-step approach), the authors identified differences in the level of population ageing in a two-dimensional space. The paper applies a new method of automatic data collection from the Local Data Bank using the bdl package and the API interface (Application Programming Interface). The BDL API is a data-sharing service through webservice defining programming interfaces independent of the programming language, whereas the bdl package using this API enables webservice integration with the R statistical environment, eliminating the need for manual data extraction and enabling the automation of recurring activities
Econometrics = Ekonometria, 2019, Vol. 23, No. 4, s. 1-15
Keywords: ageing; multidimensional scaling; aggregate measures; R program; starość; skalowanie wielowymiarowe; miary agregatowe; program R